Capillary malformation/arteriovenous malformation syndrome. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The CM/AVM syndrome (1) is important because in 7% of cases it is associated with cerebral and spinal AVM and is the most frequent cause of cerebral hemorrhages in the child. You have to think about it when you see at least 3 pink spots of a few centimeters randomly distributed, present at birth or arising in the first years of life, sometimes associated with an ischemic halo, hyperpigmented background under pressure of the fingers, hypertrichosis and underlying arteriovenous malformations, detectable at palpation (thrills, pulsations) or colordoppler. CM/AVM is transmitted by an autosomal dominant trait and therefore it is often familial. CM/AVM is related to a mutation of RASA1 or more rarely of EPHB4 (2). It is debatable to do MRI in all children with CM/AVM because AVM can also be formed later and their early identification does not change the prognosis of affected children due to the poor therapeutic possibilities.